The Teachers’ Voice in Syllabus Design - Nehru P. Pongsapan (Teaching English as a Foreign Language Overseas Journal, 2016)
If curriculum is to reflect the goals of a nation and the needs of its students, itmakes sense for teachers to participate in its creation. In fact, curriculum designhas long been associated with the idea of teacher contribution. The presenteffort tries to prove that EFL teachers can be active participants rather thanpassive recipients. They can convey vital information to curriculum designersinstead of being blindly subjected to a highly centralized educational system.The study also provides a consideration of role requirements and thecompetencies of teachers as curriculum leaders. The data collected from semistructuredinterviews indicate that teachers are neither involved nor informed inthe process of curriculum design and that their engagement is merely withintheir own classrooms walls. Although they play a central role in the process ofeducation, yet they miss the passion of belonging as little attention, if any, isgiven to their voices.